2009
DOI: 10.1007/s00018-009-8670-0
|View full text |Cite
|
Sign up to set email alerts
|

Misregulated RNA Pol II C-terminal domain phosphorylation results in apoptosis

Abstract: Misregulation of the level of RNA polymerase II carboxyl-terminal domain (CTD) phosphatase, Fcp1, in Drosophila results in high level of caspase-mediated apoptosis. Apoptosis induction by Fcp1 misregulation requires the presence of Drosophila melanogaster (Dm)p53, but occurs without the transcriptional activation of Dmp53 proapoptotic targets rpr, ark, and hid. Overproduction of a transcription activation-defective mutant Dmp53 protein increases, while Dmp53 null background decreases significantly the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In accordance with this, the human p53 protein has been reported to associate with coding regions of RNAPII-transcribed genes in a heterologous system32. It was previously shown that Dmp53 ( Drosophila melanogaster p53) was localised at transcriptionally active regions on the Drosophila polytene chromosomes and that the phosphorylation state of RPB1 CTD influenced its localisation33.…”
mentioning
confidence: 74%
“…In accordance with this, the human p53 protein has been reported to associate with coding regions of RNAPII-transcribed genes in a heterologous system32. It was previously shown that Dmp53 ( Drosophila melanogaster p53) was localised at transcriptionally active regions on the Drosophila polytene chromosomes and that the phosphorylation state of RPB1 CTD influenced its localisation33.…”
mentioning
confidence: 74%
“…Overexpression or silencing of CTDP1 may inhibit its associated regulation mechanisms. Schauer et al (16) found that FCP1 misregulation, whether FCP1 overexpression or silencing, induced p53-dependent and enhanced levels of caspase-mediated apoptosis in Drosophila melanogaster. The present study also found that CTDP1 silencing induced an increase in the apoptotic rate of GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that death-receptor, mitochondria and endoplasmic reticulum played an important role in apoptosis (8,9). The activation of effector caspases such as caspase-3 and -7 by initiator caspases (caspase-8 and -9) are responsible for the cleavage of cellular substrates degrading the chromosomes into nucleosomal fragments during apoptosis (10,11). Two major pathways are involved in cell apoptosis; the death receptor pathway and the mitochondria-dependent pathway.…”
Section: Introductionmentioning
confidence: 99%